2015
DOI: 10.1007/s11011-015-9739-0
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, leptin and IL-1 β in elderly diabetic patients with mild cognitive impairment

Abstract: The aim of the study was to determine the serum levels of adiponectin, leptin and IL-1 β in elderly diabetic patients with and without mild cognitive impairment (MCI) and to examine the associations of these markers with clinical and cognitive parameters. A biochemical evaluation was performed of 62 seniors with type 2 diabetes (T2DM) and MCI, and 132 seniors with T2DM but without MCI (controls). Serum leptin and IL-1 β levels were higher and adiponectin concentration was lower in MCI patients than controls. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 46 publications
(53 reference statements)
4
40
0
Order By: Relevance
“…Two studies reported on low adiponectin levels in T2DM patients who had reduced gray matter volume, hippocampal volume and glucose metabolism, to be consistent with Alzheimer’s disease pathophysiologies [79,82]. Another group reported that T2DM patients with MCI had lowered serum adiponectin levels [83]. Besides human patients, Kurata et al showed the reduction of serum APN levels in APP transgenic mice [84].…”
Section: Pathophysiological Roles Of Adiponectin In Alzheimer’s DImentioning
confidence: 94%
“…Two studies reported on low adiponectin levels in T2DM patients who had reduced gray matter volume, hippocampal volume and glucose metabolism, to be consistent with Alzheimer’s disease pathophysiologies [79,82]. Another group reported that T2DM patients with MCI had lowered serum adiponectin levels [83]. Besides human patients, Kurata et al showed the reduction of serum APN levels in APP transgenic mice [84].…”
Section: Pathophysiological Roles Of Adiponectin In Alzheimer’s DImentioning
confidence: 94%
“…Moreover, adiponectin exerts a protective role in several pathologies, such as cardiovascular diseases, cancer, and appears also to promote longevity (Yamauchi & Kadowaki, ). However, after the discovery of adiponectin in human cerebrospinal fluid (Kos et al, ), the adiponectin system gained attention and several clinical studies suggested a role in neuropsychiatric diseases, such as depression (Leo et al, ; Narita et al, ), cognitive impairment associated with diabetes (Gorska‐Ciebiada et al, ; Masaki et al, ), Alzheimer's disease (Teixeira et al, ), stroke (Sasaki et al, ), multiple sclerosis (Musabak, Demirkaya, Genç, Ilikci, & Odabasi, ) and attention deficit hyperactivity disorder (Mavroconstanti, Halmøy, & Haavik, ). In particular, those studies have all reported lower circulating levels of adiponectin.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have associated diabetes mellitus with increased risk of dementia. [13][14][15][16] A cohort of 71,433 diabetes mellitus patients followed for 11 years supports this association. 17 Diabetes mellitus can accelerate the conversion of Mild Cognitive Impairment (MCI) to dementia.…”
Section: Introductionmentioning
confidence: 78%